P1361Impact of radiation/chemotherapy for breast cancer on the electroanatomic features in patients receiving catheter ablation for left atrial arrhythmia. (18th June 2020) - Schenker, N; Hashiguchi, N; Maurer, T; Lemes, C; Rottner, L; Reissmann, B; Rillig, A; Kuck, K H; Ouyang, F; Mathew, S
Abstract: Background: Atrial fibrillation (AF) is a common cardiac arrhythmia and catheter ablation a viable treatment option for patients with AF. Extensive left atrial (LA) scars, frequently seen in patients with persistent AF, can limit its efficacy. Radiation for breast cancer treatment is known to have serious long-term effects (e.g. fibrosis) on the targeted tissue. At the same time, chemotherapy often leads to organ dysfunction. We sought to examine the effects of radiation and chemotherapy on the electroanatomic features of the LA in patients who received catheter ablation for left atrial arrhythmias with prior breast cancer treatment. Methods and Results: We compared 38 patients (mean age 68.4 ± 7.1 years) who underwent catheter ablation for LA arrhythmia and had a previous diagnosis of breast cancer with 38 patients (mean age 65.4 ± 7.3 years) without breast cancer who formed our control group. LA scar area, as well as its distribution was measured during the electrophysiology (EP) study and graded according to the Utah classification. The existence of LA scarring did not differ significantly between both groups (71.1% vs. 76.3%, p = 0.602). LA scar area (excluding PVs) was 107.5cm2 ± 19.0cm2 in the breast cancer group compared to 110.1cm2 ± 18.5cm2 in the control group (p = 0.536). The distribution of the scar area revealed no significant difference between both groups, however an involvement of the anterior wall was common (65.8% vs. 73.7%; p = 0.454). We further investigated whether the location of breast cancer had an impact on the LA scar development of the patients in our study cohort. Here, we found no significant difference in the amount of LA scarring when comparing patients with left-sided breast cancer to patients with right-sided breast cancer (66.7% vs. 73.9%). In a sub-analysis patients with breast cancer and persistent AF showed a non-significant trend towards greater LA scar areas (17.4cm2 vs. 6.8cm2) in comparison to patients of the control group with similar LA volumes. The patient's age (>65 years) was the only independent predictor for greater LA scarring we could identify. Neither former radiotherapy, nor chemotherapy showed a positive correlation with greater LA scarring. Conclusion: There is no change in the distribution as well as an increase of the extent of LA scars after thoracic irradiation and/or chemotherapy. A trend towards greater LA scar areas was seen in patients with breast cancer and persistent AF. The patient's age was identified as an independent predictor for LA scar development.